Analisis Tipe Longsoran Daerah Pohe Kota Gorontalo Berdasarkan Orientasi Struktur Geologi - Usman, Fatma T.; Arifin, Yayu Indriati; Hutagalung, Ronal; Permana, Aang Panji (Journal of Applied Geoscience and Engineering, 2022)
Administratively, the research area is located in Pohe Village, Hulonthalangi sub-district, Gorontalo City, Gorontalo Province. Astronomically, the research area is at coordinates 00030'16.10"- 00030'41.58" north latitude and 12302'36.10"- 12303'19.55" east longitude. The purpose of this study was to analyze the type of landslide based on the orientation of the geological structure of the Pohe area and the type of landslide based on the orientation of the geological structure of the Pohe area. The method used in this research is retrieval of field data, namely lithological data, geological structure data and slope data of the research area, then structural data processing using dips 6.0 software application and analyzed using stereographic projections. Based on the results of identification and stereographic analysis, it shows that in the research area there are 2 types of landslides, namely plane failure and toppling failure. The type of plane failure is found at stations 1.1, 1.2, 1.3, 1.4, and 1.6. While the type of landslide toppling failure is found at stations 1.5, 1.7, and 1.8.